All-in-one Novell 5 CNA/CNE exam guide - Mueller, John Paul (McGraw-Hill, 2000)
All-in-One-format--Covers both the CNA and CNE exams under one cover, including all versions of NetWare, including 4.x, IntranetWare, and GroupWise. On-the-job case studies--Each chapter brings the experience factor into play with case studies. These help readers ace questions on SoftSolutions and Informs. Interactive CD-ROM--Includes hundreds of study questions, a "fun test," and a Jeopardy-like game on the CD-ROM to help Novell candidates study in different ways.